KOMPETENSI ABSOLUT TERKAIT KASUS RAHASIA DAGANG (Analisis Putusan Nomor 280/Pdt.G/2008/PN.Bks jo Putusan MA Nomor 1713K/Pdt/2010) - Qaysha Innaya Sasqi, (2023)
The background of this research is the existence of the Supreme Court decision No. 1713K/Pdt/2010 which discusses the trade secret dispute that occurred between PT. Basuki Pratama Engineering (BPE) as the Plaintiff against PT. Hitachi Construction Machinery Indonesia (HCMI) as the Defendant. Where the Panel of Judges of the Supreme Court granted the cassation request filed by the Plaintiff with legal considerations related to the absolute competence of the district court to decide cases of trade secret disputes and not the authority of the commercial court. This study analyzes the problem of disclosing Trade Secret information and legal protection against such violations in accordance with the provisions stipulated in Law Number 30 of 2000 concerning Trade Secrets. This study uses a normative juridical method with literature studies, a statutory approach, and a case approach through an analysis of the substance of court decisions. So it is concluded that the settlement of Trade Secret disputes can be carried out in district court due to the nature of Trade Secrets which cannot be known by the public. Meanwhile, commercial courts always have trials that are open to the public.